Identifikasi Kandungan Senyawa Antioksidan Sebagai Agen Anti-Aging Pada Minyak Atsiri Cascara Kopi Robusta (Coffea canephora) - Naomi Aprisa; Diky Setya Diningrat (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
Coffee cascara, often considered waste, contains bioactive compounds with antioxidant potential. This study aimed to identify antioxidant compounds in essential oil from Robusta coffee cascara green bean and evaluate their activity. Extraction was performed using the Soxhlet method with 96% ethanol, followed by GC-MS analysis, PubChem and PASS Online evaluation, and antioxidant testing using the DPPH method. A total of 20 compounds were identified, mainly volatile phenolics, alkaloids, and heterocyclics. Quinic acid showed the highest antioxidant potential, while the IC50 value of 15.78 mg/L indicated very strong antioxidant activity. These results suggest that cascara essential oil from Robusta coffee green bean is a promising anti-aging agent.